Effect of continuous fiber orientations on quasi‐static indentation properties in 3D printed hybrid continuous carbon/Kevlar fiber reinforced composites. (1st February 2023) - Zhu, Wanying; Li, Shixian; Peng, Yong; Wang, Kui; Ahzi, Said
Abstract: The mechanical properties of hybrid continuous carbon and Kevlar fibers reinforced polyamide (PA)‐based composites manufactured by the fused deposition modeling (FDM) technique were investigated in this paper. The effects of fiber raster orientations, fiber layer locations, and stacking sequences were studied by the quasi‐static indentation (QSI) tests. The multi‐scale morphological investigation was applied to analyze the deformation and failure mechanisms of the printed hybrid composites. The results showed that the printed hybrid composites with 0°/90°/0°/90° fiber raster orientations and the middle fiber layer locations presented the highest energy absorption as high as 5107.0 N mm in the current study. In contrast, the printed hybrid composites with 0°/45°/90°/135° fiber raster orientations and the bottom fiber layer locations performed the lowest energy absorption of 3659.5 N mm. 0° continuous fiber layers with effective long raster lengths could effectively improve the crack resistance of specimens. The introduction of 90° continuous layers into laminates significantly increased the energy absorption capability of specimens due to the extensive damage of continuous fiber‐reinforced layers (CFRLs). CFRLs with the middle location helpfully delayed the initiation and propagation of cracks. In addition, when CFRLs were located at the top and bottom, the specimens with Kevlar fiber layers above carbon fiber layers showed much higher maximum force than that of specimens with Kevlar fiber layers below carbon fiber layers.